OPTIMIZING THE DESIGN OF COMPLETE DENTURES FOR PROSTHETIC STOMATITIS PREVENTION - A.A. Zverkhanovskyi; A.V. Yarova; P.V. Maksimenko (Ukrainian Medical Stomatological Academy, 2016)
The aim of the paper is to evaluate the impact of the developed design with the use of amaranth oil of the mucous membrane of oral cavity and hard tissues of the alveolar bone. Materials and Methods. 114 patients were divided into 3 groups depending on the methods of prosthetic stomatitis prevention. Complete removable acrylic dentures were made to all patients. The first group (32 patients) included patients with symptoms of traumatic prosthetic stomatitis whom was administered "Rotokan" during the first 7 days of prosthesis's use, enhanced hygiene of the prosthesis was recommended. The second group (36 patients) contained patients whom course of prevention amaranth oil after the prosthesis was prescribed. The third group included patients with complete dentures which were made with a modified basis, and who used our method of prevention of prosthetic stomatitis with amaranth oil. To identify the place of inflammation of the mucous membrane it was used method which was developed by N.I. Lisovykh. The method is based on macrohistohimical reaction with Schiller-Pisarev solution and 1% solution of toluidine blue. Definition of atrophy of the alveolar processes of the jaws was performed by the method of determination of alveolar atrophy which was developed at the Department of Prosthetic Dentistry of Odessa Medical University. Results. The use of modified basis for stomatitis prevention reduces the inflammatory manifestations of prosthetic stomatitis, prevents the emergence of chronic prosthetic stomatitis, and application of permanent effects of oil on the oral mucous membrane, increases anti-inflammatory efficacy of amaranth oil. The use of amaranth oil for stomatitis prevention causes decrease of speed of atrophy of alveolar processes in immediate periods (on 139,4%) and in regions on 175% (18 months). The use of the modified surface of the denture base with amaranth oil reduces the rate of atrophy on 43.6% and 328.8%, respectively. Conclusions: the basis for the prevention of prosthetic stomatitis with amaranth oil has significantly reduced the degree of inflammatory response by mucosal prosthetic bed on 24.46%. Use of the modified surface with the prosthetic amaranth oil base reduces atrophy rate on 43.6%.